Land tenure status based pesticide use knowledge of vegetable farmers. Issue 3 (4th May 2022) - Shahbaz, Pomi; Ul Haq, Shamsheer; Boz, Ismet; Aziz, Babar
ABSTRACT: Owner farmers and tenant farmers have different income generating strategies related to vegetable production. It is important to know the differences between these two group farmers regarding pesticide use practices and awareness, as well as the factors influencing their knowledge of pesticide use practices. This study examined effects of land tenure status on vegetable farmer knowledge of pesticide use practices, health effects, and environmental effect of pesticides. A total of 211 owner and 173 tenant vegetable farmers from 7 districts were selected through a multistage sampling technique in 2019. More owners than tenants disposed of empty pesticide containers properly, but still a large proportion of both groups were using containers to store food. The owners have a higher knowledge of safe pesticide use practices, and greater information on environmental and health effects associated with pesticides in vegetables. It is necessary to put more emphasis on tenant farmers, as well as on the significant variables obtained from the econometric model of this study. The status of the grower has importance when use and disposal of pesticides is a concern with owners, who likely have greater respect for ownership and preservation of the land within the family, are more aware of uses and concerns involved with pesticides.